3D printed self-similar AlSi10Mg alloy hierarchical honeycomb architectures under in-plane large deformation. (July 2021) - Zhang, Yuwu; Lin, Yuliang; Li, Ying; Li, Xiangcheng
Abstract: Self-similar hierarchical honeycombs with complicated cellular topologies are promising cores for lightweight sandwich structures ascribed to superior structural efficiency in terms of mitigating damage. In this paper, the in-plane compressive characteristics of AlSi10Mg alloy hierarchical honeycombs, fabricated using Selective Laser Melting (SLM) methodology, under large deformation are reported. The results suggest that higher hierarchies enhance the elastic modulus of honeycombs significantly, whereas the compressive strength is improved negligibly. There is a failure mechanism transition from cell wall bending dominated to cell wall fracture dominated with the increase of relative density and hierarchical order, and the failure mechanisms are related to the wall thickness with critical value of 0.345 mm. It is concluded that the in-plane failure of hierarchical honeycombs is dominated by the bending, axial compression and shear deformation of original unit cell walls. Besides, the parent material without heat treatment contributes to more excellent mechanical properties of hierarchical honeycombs owing to higher tensile strength and elastic modulus. This work enables to facilitate the structural design and optimization of high-performance hierarchical honeycomb metamaterials with desired properties and functions. Highlights: The SLM fabricated self-similar hierarchical honeycombs topologies are investigated under in-plane compression, and the existing theoretical predictions are examined. The failure mechanism experiences a transition from cell wall bending to cell wall fracture with the increase of relative density and hierarchical order. The addition of unit cell refinement enhances the elastic modulus of AlSi10Mg alloy honeycombs significantly, whereas influences the compressive strength negligibly. The non-heated treated hierarchical honeycombs possess more excellent mechanical properties than the heat treated honeycombs, stemming from the effect of parent material.